Effects of a small fish cage farm on zooplankton assemblages (Cladocera and Copepoda: Crustacea) in a sub-tropicalreservoir (SE Brazil). - Zanatta, Augusto S.; Perbiche-Neves, Gilmar; Ventura, Robson; Ramos, Igor P.; Carvalho, Edmir Daniel [UNESP] (My University, 2010)
In Brazil, the environmental impacts of fish cage farming in water reservoirs have not been well studied. As this activity is being increasingly practiced, investigations on the impacts of this practice are strongly needed. The goal of this study was to investigate the effects of a small cage tilapia farm on zooplankton assemblages in an oligo/mesotrophic reservoir (Jurumirim Reservoir, Paranapanema River). Zooplankton, limnological variables, and water samples were obtained trimonthly during a year at two sample sites, one was located adjacent to the cage farm and the control area was located one kilometer away from it. Eighteen species were identified and Cladocera was the dominant group. The same species of microcrustaceans were identified at both sites. Among the ecological attributes studied, only evenness showed a tendency towards being higher in the control site. Significant differences between studied variables in the sites were observed only for material in suspension. The results of the study indicate that, during the studied period, the cage farm did not generate detectable changes in the zooplankton assemblages and their ecological attributes. However, small differences in some limnological variables could be an indication of some environmental changes associated with the fish farm system.